2020
DOI: 10.1186/s12889-020-09507-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety, depression and post-traumatic stress disorder among Ebola survivors in northern Sierra Leone: a cross-sectional study

Abstract: Background There is limited data available on the long-term mental health impact of Ebola virus disease (EVD) on survivors despite the disease experience of survivors meeting the criteria of a traumatic event as defined in the Diagnostic and Statistical Manual of Mental Disorders version IV (DSM IV). This study aimed to assess the prevalence and predictive factors of anxiety, depression and posttraumatic stress disorder among EVD survivors, approximately 2 years after discharge from the Ebola treatment centre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 54 publications
2
49
1
Order By: Relevance
“…Today, IU has become a popular concept to explain anxiety, many studies have found robust associations between IU and various anxiety-related conditions, and differences in an individual's ability to tolerate uncertainty affects the level of anxiety (Nicholas et al, 2007 ; Boelen and Reijntjes, 2009 ; Carleton et al, 2013 ; Norr et al, 2013 ; Oglesby and Schmidt, 2017 ). Anxiety is a typical negative emotional state of people facing emergencies, such as fear of infection in the case of major infectious diseases, e.g., COVID-19 (Cao et al, 2020 ), EBoV (Bah et al, 2020 ), H1N1 (Taha et al, 2014 ), and SARS (Li et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Today, IU has become a popular concept to explain anxiety, many studies have found robust associations between IU and various anxiety-related conditions, and differences in an individual's ability to tolerate uncertainty affects the level of anxiety (Nicholas et al, 2007 ; Boelen and Reijntjes, 2009 ; Carleton et al, 2013 ; Norr et al, 2013 ; Oglesby and Schmidt, 2017 ). Anxiety is a typical negative emotional state of people facing emergencies, such as fear of infection in the case of major infectious diseases, e.g., COVID-19 (Cao et al, 2020 ), EBoV (Bah et al, 2020 ), H1N1 (Taha et al, 2014 ), and SARS (Li et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that infectious disease outbreaks, akin to major disasters, can be traumatizing for some individuals leading to the development of PTSD. For instance, it was found that the prevalence rate of PTSD was more than 20% among the survivors of Ebola virus disease and severe acute respiratory syndrome (SARS) two years or later since the pandemic ( Bah et al, 2020 ; Mak et al, 2009 ). Not only does the pandemic affect the patients who are at imminent threat to their physical health, but it can also be a collective traumatic experience for ordinary people.…”
Section: Introductionmentioning
confidence: 99%
“…Of this figure, 350,000 have psychotic-related drug and alcohol abuse problems or illnesses such as cerebral malaria, more than 20,000 are suffering from bipolar manic depression disorder, and about 175,000 are experiencing epilepsy or schizophrenia. Most recently, Bah et al [ 35 ] emphasised the seriousness of post-traumatic stress disorder (PTSD), psychosis and depression amongst victims of the civil war, Ebola and substance abuse. It has been estimated that 10% of the country’s population, including children and young people, are suffering from PTSD.…”
Section: Background and Contextmentioning
confidence: 99%